The translation of similes in Shahnon Ahmad’s Ranjau Sepanjang Jalan into English / Nurul Nabilah Mohamad Mokhtar - Nurul Nabilah, Mohamad Mokhtar (2016)
This is a comparative study of the similes between Shahnon Ahmad’s novel entitled, Ranjau Sepanjang Jalan and its translation into English by Adibah Amin entitled, No Harvest but a Thorn. The objectives of this study are to identify the strategies used in the translation of similes from Ranjau Sepanjang Jalan into No Harvest but a Thorn and to investigate to what extent similes found in Ranjau Sepanjang Jalan can be translated as similes in No Harvest but a Thorn. The methodology of this study includes first, identifying similes in the translation of Shahnon Ahmad’s Ranjau Sepanjang Jalan into No Harvest but a Thorn based on the Malay definition of simile. Second, categorising the similes based on Pierini’s (2007) typology. Third, analysing the translation strategies based on Pierini’s (2007) strategies in translating similes. Finally, the researcher examines how far the meanings of the similes found in Ranjau Sepanjang Jalan are effectively conveyed in No Harvest but a Thorn. Research findings indicate that most of the Malay similes in this novel can be translated into English and most of the meanings of the source language (SL) text similes can be conveyed in the target language (TL) text. Thus, it can be said that the translator is quite successful in the translation of this novel. Thus, this study hopes to fill in the gap on the translation of Malay similes and provide new insights in this kind of research.